Síntese, caracterização e estudo da auto-associação em solução aquosa de derivados anfifílicos zwiteriônicos de quitosana - Barbosa, Hellen Franciane Gonçalves [UNESP] (2013)
This work presents the synthesis, characterization and self-association study of amphiphilic zwitterionic derivatives of chitosan in aqueous solution as potential drug delivery systems. Amphiphilic derivatives were obtained from deacetylated and degraded chitosan, followed by Michael addition reaction with the monomer 1-(3-sulfopropyl)-2-vinylpyridine hydroxide (SPP). The hydrophilic derivative was further modified with dodecyl groups (DD) by reductive amination reaction. The degrees of substitution (DS) by DD and SPP groups were determined using H1-NMR, and FTIR and potentiometric titration techniques were used to characterize chitosan and its derivatives. The degrees of substitution by SPP were 36 and 46 % and by dodecyl groups varied from 2 to 10%. The average molecular weights were determined using the gel permeation chromatography (GPC). The study of the selfassociation in aqueous solution was performed by using fluorescence spectroscopy, UV-Vis, dynamic light scattering (DLS) and transmission electron microscopy (TEM) techniques. The hydrophilic derivatives were soluble in all pH range and the amphiphilic derivatives exhibited self-association behavior similar to conventional surfactants. The critical aggregation concentrations, determined from pyrene fluorescence, varied from 0.005 to 0.017 g l-1 and were shown to decrease with both, the increasing hydrophobic content and pH. DLS measurements showed that self-association of the amphiphilic derivatives leads to formation of aggregates having diameters varying from 100 to 1000 nm and the zeta potential varied according with the pH. The TEM images showed spheroidal aggregates of varied sizes in accordance with DLS measurements. Quercetin was used as a model for drug loading study and the results showed that solubilizing capacity increased from 17 to 54% with the hydrophobic content of the ...